2012
DOI: 10.1007/s00125-012-2508-2
|View full text |Cite
|
Sign up to set email alerts
|

Induced pluripotent stem cells generated from diabetic patients with mitochondrial DNA A3243G mutation

Abstract: Aims/hypothesis The aim of this study was to generate induced pluripotent stem (iPS) cells from patients with mitochondrial DNA (mtDNA) mutation. Methods Skin biopsies were obtained from two diabetic patients with mtDNA A3243G mutation. The fibroblasts thus obtained were infected with retroviruses encoding OCT4 (also known as POU5F1), SOX2, c-MYC (also known as MYC) and KLF4. The stem cell characteristics were investigated and the mtDNA mutation frequencies evaluated by Invader assay.Results From the two diabe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
59
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 82 publications
(63 citation statements)
references
References 50 publications
4
59
0
Order By: Relevance
“…We found that a rapid bimodal shift toward wild-type or mutant homoplasmy occurred upon reprogramming in MELAS iPSCs, replicating findings of recent reports (40,41). Rapid shifts in mitochondrial heteroplasmy have been observed to occur in germ line (i.e., stem cells) in cows (42,43), in human patients (44,45), in mice with heteroplasmic neutral or potentially pathogenic mtDNA variants (18,25,34), and in primates (46).…”
Section: Discussionsupporting
confidence: 87%
“…We found that a rapid bimodal shift toward wild-type or mutant homoplasmy occurred upon reprogramming in MELAS iPSCs, replicating findings of recent reports (40,41). Rapid shifts in mitochondrial heteroplasmy have been observed to occur in germ line (i.e., stem cells) in cows (42,43), in human patients (44,45), in mice with heteroplasmic neutral or potentially pathogenic mtDNA variants (18,25,34), and in primates (46).…”
Section: Discussionsupporting
confidence: 87%
“…Examples of specific conditions for which patient-specific iPS cells have been obtained and differentiated into disease-relevant cell types include Parkinson's disease (Byers et al, 2012;Jang et al, 2012) and other neurodegenerative disorders Jung et al, 2012), Wilson's disease (Yi et al, 2012), lysosomal storage disorders (Huang et al, 2012b), and diabetes (Fujikura et al, 2012).…”
Section: Disease Models From Patient-specific Reprogrammed Cellsmentioning
confidence: 99%
“…Disease Modeling Using Patient-Specific iPSCs To date, several patient-specific iPSC lines have been generated from patients with a wide variety of mainly monogenetic, early-onset diseases such as neurologic disorders, 44,45) heart disease, 46,47) metabolic disease, 48) hematologic disorders, 49) mitochondrial disease, 50) chromosomal abnormalities, 51) telomere disease, 52,53) sensory organ disorder, 54) and storage disease.…”
Section: Generation Of Patient-specific Ipscsmentioning
confidence: 99%